Factors Affecting the Sustainability of MSMEs in the Tasikmalaya Indonesian Muslim Community - Lina Marlina; Sudana Sudana; Asep Saepuloh; Sinta Verawati Dewi; Kartawan Kartawan (Cita Konsultindo Research Center, 2024)
The study aims to examine how religiosity, Information and Communication Technology (ICT) usage, and the environment impact the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the Muslim community of Tasikmalaya, Indonesia. It also investigates how motivation and competitive advantage act as intermediary factors affecting this relationship. The research employs a quantitative path analysis method, collecting data through questionnaires from Muslim MSME owners and managers in Tasikmalaya. The findings indicate that religiosity, ICT usage, environment, motivation, and competitive advantage all significantly affect MSME sustainability. Moreover, religiosity, ICT usage, and environmental factors notably influence motivation and competitive advantage. Motivation and competitive advantage serve as mediators between religiosity, ICT usage, environment, and MSME sustainability. This study contributes to understanding the impact of religiosity on MSME sustainability in Tasikmalaya and sheds light on the environmental factors affecting MSMEs in Muslim communities.